Health‐related quality of life in genotype 1 treatment‐naïve chronic hepatitis C patients receiving telaprevir combination treatment in the ADVANCE study. Issue 2 (3rd June 2013) - Vera‐Llonch, M.; Martin, M.; Aggarwal, J.; Donepudi, M.; Bayliss, M.; Goss, T.; Younossi, Z.
Summary Background Chronic hepatitis C virus (HCV) infection and its treatment impact patients' health‐related quality of life (HRQL). Aim To report on treatment impact and predictors of HRQL among treatment‐naïve patients with genotype 1 chronic HCV infection who received 12‐week telaprevir (T) with 24 (T12PR24) or 48 weeks (T12PR48) peginterferon alpha‐2a/ribavirin (PR), or 48 weeks of PR in the ADVANCE study. Methods The EQ‐5D‐3L (EQ‐5D) questionnaire (index range: 0–1) was completed at baseline and weeks 4, 12, 24, 36, 48 and 72. Patients indicated their health state on five dimensions: mobility, self‐care, usual activities, pain/discomfort and anxiety/depression. Descriptive statistics for the EQ‐5D index and descriptive system and area under the curve from baseline to week 12 were calculated. Predictors of EQ‐5D index were identified using multivariate analyses. Results Data from 722 patients were included. The mean EQ‐5D index decreased during the first 12 weeks and returned to baseline by week 72 (T12PR24 by week 36) across treatments. In multivariate analysis, sustained virological response (SVR) at week 72 was associated (P < 0.0001) with improved EQ‐5D index [mean; SVR+ (0.90), SVR− (0.86)], a 4% difference, within the published range of minimal clinically important difference. Conclusions Post hoc analyses of data from ADVANCE suggested that HRQL worsened during the first 12 weeks of therapy and returned to baseline by week 72 across treatments. Improvements were observed early following completion of a 24‐week treatment (T12PR24). Telaprevir combination therapy was associated with slightly higher reductions in HRQL during the first 12 weeks (vs. PR). SVR was a statistically significant and meaningful predictor of HRQL at week 72.